Monga in northern region of Bangladesh: a study on peoples survival strategies and coping capacities (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
The objective of this paper is to explore peoples survival strategies and coping capacities to combat monga at household level in the northern region of Bangladesh. The agriculture based rural economy, extreme poverty, highpercentage of landless, lack of sufficient caloric intake, unemployment of vast agricultural labour force etc. are the root causes of vulnerability to monga in the northern regions specifically few districts of greater Rangpur. Moreover, geographically this region is vulnerable to natural hazards such as floods and droughts. The past records of food shortages and famine reveal that the trend is still continuing in the monga-prone areas. The present study found that the most vulnerable groups in the monga-prone areas were agricultural wage labourers, landless and marginal farmers, female headed households, children, pregnant women and aged people. The present study also found that with a view to cope with the monga, various coping strategies such as selling of labour with advance payment at cheap rate, borrowing of money, selling of assets, looking for work in other areas, dependency on relief, selling of field crops in advance at cheap rate etc. were adopted by the affected households. The present study also found that coping capacity was associated with household heads socio-economic status e.g. level of education, monthly income, types of occupation, etc. Vulnerability to monga was higher for the illiterate and low income groups than the educated andhigh income groups. The present study argues that the policy makers ofGovernment and NGOs should emphasize on enhancing of coping capacities of poor and marginalized groups through rural centric development, ruralemployment generation, maximum utilization of agricultural land, proper credit support and agro-based industrialisation in the northern Bangladesh.